Sanksi Pidana Terhadap Pelaku Pencemaran Konservasi Sumber Daya Alam - Putu Nandita Dewi; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Analogi Hukum, 2025)
Indonesia is abundant with rich natural resources. The natural resources available in Indonesia provide many uses for humans. Due to their irreplaceable nature and vital role for human life, conservation of natural resources is an absolute responsibility for every generation. Currently, conservation efforts are the most discussed topic of conversation. This research is a normative type of legal research, meaning that this research begins with a deductive analysis of the provisions in the governing legislation. The results show that environmental protection for natural resource conservation is regulated in Law No. 5 of 1990. In addition, the law also regulates criminal sanctions for violators who pollute natural resources. Law No. 5 of 1990 contains legal provisions relating to rights, obligations, and authorities in an effort to protect and manage natural resources. Criminal sanctions are a form of punishment that aims to ensure that legal rules regarding natural resource conservation management are respected and adhered to in accordance with the law.